Manfaat Kayu Ulin - Satria Agung Wardani (STIKes Ibnu Sina Ajibarang, 2024)
Ulin wood (Eusideroxylon zwageri) or commonly called iron wood is one of the famous and strongest woods in its habitat Kalimantan forest. There are various regional names for Ulin, including bulian, bulian rambai, onglen (South Sumatra), belian, tabulin, telian, tulian and ulin (Kalimantan) (Abdurachman, 2011). Ulin (Eusideroxylon zwageri) or also known as bulian or ironwood is a woody tree and is a typical plant of Southeast Asia including Indonesia (Sumatra & Kalimantan), Malaysia (Sabah & Sarawak), Philippines (Sulu Islands). Ulin is classified into the Lauraceae tribe. Ulin has a typical tree height of 30-35 m, diameter at breast height (dbh) 60-120 cm. Straight trunk with branches, round and tight crown and horizontal branching. Ulin generally grows at an altitude of 5 - 400 m above sea level with flat to sloping terrain, growing scattered or clustered in mixed forests but very rarely found in swamp habitats Ulin wood is also resistant to changes in temperature, humidity, and the influence of sea water so that the nature of the wood is very heavy and hard. somewhat separated from other trees and surrounded by a circular path of ironwood. At the bottom of the ulin tree there is a hollow section. Ulin grows well in wet tropical forests, on non-waterlogged soils up to 500-625 meters above sea level, in flat areas near rivers and tributaries, undulating areas to ridges. The soil where ulin grows is generally sandy with low pH and macro nutrients (N, P, K).